2003
DOI: 10.1097/00005537-200310000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Presbycusis: A human temporal bone study of individuals with flat audiometric patterns of hearing loss using a new method to quantify stria vascularis volume

Abstract: Objective: The purpose of this study was to determine the prevalence of stria vascularis atrophy in individuals with presbycusis and flat audiometric patterns of hearing loss. Individuals with presbycusis have historically been categorized by the shape of their audiograms, and flat audiometric thresholds have been reported t o be associated with atrophy of the stria vascularis. Stria vascularis volume was not measured in these studies. Study Design:Retrospective case review. Methods: Archival human temporal bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 72 publications
4
33
0
Order By: Relevance
“…This explains the difficulty of associating specific clinical symptoms or signs with specific anatomic locations [9][10][11]. Much of the current research focuses on finding underlying genetic abnormalities that may cause, contribute to, or predispose to the development of this disease.…”
Section: Discussionmentioning
confidence: 99%
“…This explains the difficulty of associating specific clinical symptoms or signs with specific anatomic locations [9][10][11]. Much of the current research focuses on finding underlying genetic abnormalities that may cause, contribute to, or predispose to the development of this disease.…”
Section: Discussionmentioning
confidence: 99%
“…12,40 One potential explanation is that changes were subcellular; at the molecular level. Indeed, molecular studies have shown a shift in expression of Na, KATPase isoforms with age in the spontaneously hypertensive rat and an increase in endolymph Kþ concentration with ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…This pattern is histologically correlated with degeneration within the stria vascularis, although reports are variable. 11,12 As described below, strial hearing loss reflects a reduced endocochlear potential, but with an intact sensory system. As such, word discrimination is commonly better than expected for the threshold of hearing.…”
Section: Presbycusismentioning
confidence: 99%
“…Human temporal bone studies have applied measures of strial thickness, volume, or area to quantify age-related strial changes, and the probable contribution of strial pathology to hearing loss (Kusunoki et al, 2004;Nelson and Hinojosa, 2003;Pauler et al, 1988;Suzuki et al, 2006). We have argued that without EP recordings these measures may over diagnose strial presbycusis (Ohlemiller, 2006).…”
Section: Consideration Of Methodsmentioning
confidence: 99%